1996
DOI: 10.1016/0378-1097(95)00500-5
|View full text |Cite
|
Sign up to set email alerts
|

Divergicin 750, a novel bacteriocin produced by Carnobacterium divergens 750

Abstract: Divergicin 750, a bacteriocin produced by Carnobacterium divergens 750, preferentially inhibited the growth of strains of Carnobacterium and Enterococcus. Selected strains of Listeria monocytogenes and Clostridium perfringens were also inhibited. The bacteriocin was purified to homogeneity by ammonium sulfate precipitation and sequential S-Sepharose, hydrophobic interaction and reversed phase chromatography. The complete amino acid sequence was determined by Edman degradation. The peptide consisted of 34 amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
0
8
0
1
Order By: Relevance
“…'lm, 1988;Gildberg et al, 1995). Both C. divergens and C. piscicola have been isolated from various fish raw materials, and it has been shown that C. divergens may produce bacteriocins (Pilet et al, 1995;Holck et al, 1996). The C. divergens grew well on the cod muscle hydrolysate medium, and total viable counts of the bacteria in newly prepared feed C was about 2 x 10 9 per g. At the end of the experiment, after storage for about one month at 4°C and thereafter for about two weeks at room temperature, the number of viable C. divergens in the feed was reduced to about 10 7 per g. According to Nousiainen & SeUilii (1993) 10 7 lactic acid bacteria per g feed is considered to be sufficient to give good probiotic effects.…”
Section: Resultsmentioning
confidence: 99%
“…'lm, 1988;Gildberg et al, 1995). Both C. divergens and C. piscicola have been isolated from various fish raw materials, and it has been shown that C. divergens may produce bacteriocins (Pilet et al, 1995;Holck et al, 1996). The C. divergens grew well on the cod muscle hydrolysate medium, and total viable counts of the bacteria in newly prepared feed C was about 2 x 10 9 per g. At the end of the experiment, after storage for about one month at 4°C and thereafter for about two weeks at room temperature, the number of viable C. divergens in the feed was reduced to about 10 7 per g. According to Nousiainen & SeUilii (1993) 10 7 lactic acid bacteria per g feed is considered to be sufficient to give good probiotic effects.…”
Section: Resultsmentioning
confidence: 99%
“…C. mobile and some strains of C. maltaromaticum did not spoil MAP shrimp (15). Some strains have been proposed as protective cultures of meat becauce they produce bacteriocins (11,14). Among the lactococci, Lactococcus piscium has been identified as a spoilage organism responsible for shortening the sensory shelf life of pork meat (25).…”
Section: Discussionmentioning
confidence: 99%
“…1988 ), 3·9 kDa leucocin A ( Hastings et al . 1991 ) and 3·5 kDa divergicin 750 ( Holck et al . 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems to aggregate with other substances or to aggregate into its polymer forms in non-denaturing conditions. Low molecular weight bacteriocins were reported for several other bacteriocins such as 5·8 kDa lactococcin A (Holo et al 1991), 2·7 kDa pediocin AcH (Bhunia et al 1988), 3·9 kDa leucocin A (Hastings et al 1991) and 3·5 kDa divergicin 750 (Holck et al 1996).…”
Section: Discussionmentioning
confidence: 99%